The microstructure of tungsten exposed to D plasma with different impurities. (August 2017) - Rasinski, M.; Kreter, A.; Torikai, Y.; Linsmeier, Ch.
Highlights: Surface morphology of W due to mixed plasma bombardment was investigated. Blistering and erosion is dependent on W grain orientation. Tritium uptake on pre-exposed plasma was measured. TEM confirms correlation between tritium uptake and near surface damage zone. Abstract: In this study the effect of impurities in deuterium plasma on the tungsten microstructure is investigated. W samples were exposed in the linear plasma generator PSI-2 at a sample temperature of 500 K with an incident ion flux of about 10 22 m −2 s −1, an incident ion fluence of 5 × 10 25 m −2 and an incident ion energy of 70 eV. Samples were exposed to pure D+ plasma and with additional impurities of He (3%), Ar (7%), Ne (10%) or N (5%). After the PSI-2 exposure a part of each sample was additionally loaded with tritium to measure the tritium uptake using the imaging plate technique. The surface morphology was investigated using scanning electron microscope (SEM) combined with a focused ion beam (FIB) utilized for cross-sectioning and thin lamella preparation for the transmission electron microscope (TEM) analysis. Blistering with grain orientation dependence was observed on all exposed samples. Most pronounced blistering is reported for grains with orientation close to (111). The addition of Ar or Ne results in surface erosion with different yields depending on grain orientation. Highest erosion yield is observed for grains with orientation close to (100). Large blisters are present but show signatures of erosion. Less pronounced erosion is visible when adding N. The highest uptake of tritium was reported for the sample exposed to D+He plasma which corresponds to the largest – 18 nm, near surface damage zone revealed by TEM. Lowest tritium accumulation was observed for samples exposed to D+Ar and D+Ne plasmas, which corresponds to the shallowest near surface damage zone, as confirmed by TEM.